Nutrition education intervention improves nutrition knowledge, attitude and practices of primary school children : a pilot study. - Mohd Shariff, Zalilah; Abu Samah, Bahaman; Paim, Laily; Ismail, Maznah; Kasim, Mohd Sham; Othman, Norlijah; Hashim, Normah; Buhari, Siti Sabariah; Jamil Osman, Zubaidah; Mohd Hussein, Zabidi Azhar (American Alliance for Health, Physical Education, Recreation and Dance, 2008)
The purpose of this study was to determine the changes in knowledge, attitude and practices of primary school children after receiving a nutrition education intervention for 6 weeks. A validated questionnaire was used to assess knowledge, attitude and practice at pre- and post-intervention. A total of 335 students from four primary schools were assigned to either intervention or comparison group. The intervention group received nutrition education taught by trained school teachers while the comparison group received the standard Health and Physical Education curriculum. A generalized linear univariate procedure was used to compare changes in knowledge, attitude and practice scores between intervention and comparison groups with ethnicity, weight-for-age, mother’s and father’s employment as confounding factors. There were significant increments (p<0.001) in the post intervention mean scores of knowledge (2.17 vs. 0.47), attitude (1.40 vs. 0.32) and practice (0.87 vs. -0.10) items for the intervention group compared to comparison group. The changes in knowledge (F=17.72, p<0.001), attitude (F=6.41, p<0.05) and practice (F=15.49, p<0.001) in the intervention group were maintained even after adjusting for confounding factors. The findings support the importance of providing children with nutrition knowledge to promote healthy dietary behaviors.